The Influence of Integrated Marketing Communication through Digital Media on Brand Loyalty of Thai Tourists Using Spa Businesses in Phuket - Noichalerm, Wanwisa; Samerpak, Tanarat (Hatyai Academic Journal, 2023)
The purposes of this research were 1) to study the perceptual level of integrated marketing communication through digital media, and 2) to study integrated marketing communication through digital media that influences brand loyalty of Thai tourists using spa businesses in Phuket. The stratified sampling method, as well as the convenient random sampling method, were used. The samples were 400 Thai tourists who used spas in Phuket. The statistics used for analysis were the mean, standard deviation, and multiple regression analysis. The results showed that the overall perception level among Thai tourists of integrated marketing communications through digital media was at a high level. By considering each aspect, it was found that the highest mean was digital sale promotion, digital personal selling, and digital direct marketing, respectively. The integrated marketing communication through digital media that influenced brand loyalty found that digital sale promotion and digital personal selling had influences on brand loyalty of using spa businesses of Thai tourists in Phuket by 37% of the variation predicted in brand loyalty.